Prognostic significance of thymidylate synthase, dihydropyrimidine dehydrogenase and thymidine phosphorylase protein expression in colorectal cancer patients treated with or without 5-fluorouracil-based chemotherapy - Soong, R.; Shah, N.; Salto-Tellez, M.; Tai, B.; Soo, R.; Han, H.; Ng, S.; Tan, W.; Zeps, Nikolajs; Joseph, D.; Diasio, R.; Iacopetta, B. (Oxford University Press, 2008)
Background: Low tumour expression levels of thymidylate synthase (TS), dihydropyrimidine dehydrogenase (DPD) and thymidine phosphorylase (TP) have been linked with improved outcome for colorectal cancer (CRC) patients treated with 5-fluorouracil (5-FU). It is unclear whether this occurs because such tumours have better prognosis or they are more sensitive to 5-FU treatment. Patients and methods: Associations between TS, DPD and TP levels, determined by tissue microarrays and immunohistochemistry, and survival was evaluated in 945 CRC patients according to treatment status. Results: Low TS and DPD expression associated with worse prognosis in stage II [hazard ratio (HR) = 1.69, 95% confidence interval (CI) (1.09-2.63) and HR = 1.92 (95% CI 1.23-2.94), respectively] and stage III CRC patients treated by surgery alone [HR = 1.39 (95% CI 0.92-2.13) and HR = 1.49 (95% CI 1.02-2.17), respectively]. Low TS, DPD and TP associated with trends for better outcome in stage III patients treated with 5-FU [HR = 0.81 (95% CI 0.49-1.33), HR = 0.70 (95% CI 0.42-1.15) and HR = 0.66 (95% CI 0.39-1.12), respectively]. Conclusion: Low TS and DPD expression are prognostic for worse outcome in CRC patients treated by surgery alone, whereas low TS, DPD and TP expression are prognostic for better outcome in patients treated with 5-FU chemotherapy. These results provide indirect evidence that low TS, DPD and TP protein expression are predictive of good response to 5-FU chemotherapy. © The Author 2008. Published by Oxford University Press on behalf of the European Society for Medical Oncology. All rights reserved.